Solid electrolyte and preparation method and application thereof

By doping non-metallic binary nitrides with non-metallic elements in Li9N2Cl3-based solid electrolyte, the problem of flammable and volatile solvents in existing secondary batteries is solved, significantly improving the ionic conductivity of the solid electrolyte, and achieving higher electrochemical performance and safety.

CN119852506APending Publication Date: 2025-04-18SUZHOU QINGTAO NEW ENERGY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411995411.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The organic carbonate solvents used in existing secondary batteries are flammable and volatile, resulting in safety risks of spontaneous combustion and explosion under high temperature or abnormal conditions, and it is difficult to develop solid electrolytes with high ionic conductivity to replace liquid batteries.

Method used

By doping non-metallic elements in the Li9N2Cl3-based solid electrolyte, a non-metallic binary nitride composed of trivalent, tetravalent or pentavalent non-metallic elements and nitrogen elements is used to replace the portion of Li3N, and the doping ratio is regulated to improve the ionic conductivity of the solid electrolyte.

Benefits of technology

It significantly improves the ionic conductivity of solid electrolytes, reduces production costs, and at the same time enhances electrochemical stability and structural stability, promoting the commercial application of solid-state battery technology.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides a solid electrolyte and a preparation method and application thereof. The chemical formula of the solid electrolyte is Li < 9-12x > M < 1 > a < x > N < 2-4x + b < x > Cl3, M < 1 > is selected from non-metallic elements, a * a < + > = 3b, a < + > is the valence of M < 1 > ions in the formula, and a < + > is 3, 4 or 5, egt; 0, bgt; the value range of x is from 0.01 to 0.1. The invention provides a solid electrolyte with low cost and high ionic conductivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of batteries, and in particular relates to a solid electrolyte and a preparation method and application thereof. Background Art

[0002] At present, large-scale commercial secondary batteries generally use flammable and volatile organic carbonate solvents as electrolytes, which leads to the safety hazard of spontaneous combustion and explosion of secondary batteries under high temperature or abnormal conditions. Therefore, using non-volatile and non-combustible solid electrolytes to replace traditional electrolytes is considered to be one of the effective means to solve the safety problem of secondary batteries.

[0003] Solid electrolytes are non-flammable, high temperature resistant, non-corrosive and non-volatile, which can fundamentally avoid problems such as electrolyte leakage and electrode short circuit in traditional secondary batteries, thereby improving the safety level of secondary batteries. In addition, solid electrolytes also have high mechanical strength and thermal stability, which can effectively inhibit the formation of lithium dendrites and prevent dendrites from piercing the diaphragm and causing short circuits.

[0004] However, in view of the electrochemical environment faced by secondary batteries during actual use, there are few reports on how to industrialize the design of solid electrolyte materials to prepare high ionic conductivity solid electrolytes and show excellent reduction resistance when matched with the negative electrode, thereby constructing solid-state batteries with stable interfaces to replace current liquid batteries. Therefore, selecting suitable solid-state electrolyte materials and optimizing their design are key steps in the development of secondary batteries. This can not only improve the energy density and safety of secondary batteries, but also promote the commercial application of solid-state battery technology.

[0005] In summary, it can be seen that there is an urgent need to develop a high-performance solid electrolyte material to improve the electrochemical performance of secondary batteries. Summary of the invention

[0006] In view of the deficiencies in the prior art, the object of the present invention is to provide a low-cost and high-ionic conductivity solid electrolyte and a preparation method and application thereof.

[0007] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0008] In a first aspect, the present invention provides a solid electrolyte, wherein the chemical formula of the solid electrolyte is Li 9- 12x M1 ax N 2-4x+bx Cl3, where M1 is selected from non-metallic elements, a×a + =3b,a + is the valence of the M1 ion, a +is 3, 4 or 5, a>0, b>0 and the value range of x is 0.01~0.1.

[0009] Preferably, the M1 is selected from one or more of silicon, boron or phosphorus.

[0010] Preferably, the M1 is selected from silicon, a + 4, the chemical formula of the solid electrolyte is Li 9-12x Si 3x N2Cl3.

[0011] In a second aspect, the present invention provides a method for preparing the solid electrolyte as described in the first aspect, the method comprising the following steps:

[0012] The solid electrolyte is obtained by mixing and ball-milling a non-metallic binary nitride containing the M1 element, Li3N and LiCl.

[0013] Preferably, the non-metallic binary nitride containing the M1 element includes Si3N4, BN or P3N5.

[0014] Preferably, the non-metallic binary nitride containing the M1 element is Si3N 4, Taking the total mass of Si3N4, Li3N and LiCl as 100%, the mass percentage of Si3N4 is 1%-10%, and more preferably 1%-5%.

[0015] Preferably, the mixed ball milling includes: a first ball milling process and a second ball milling process.

[0016] Preferably, the rotation speed of the first ball milling treatment is 150 rpm / min to 200 rpm / min, and the time of the first ball milling treatment is 1 h to 3 h, more preferably 2 h.

[0017] Preferably, the rotation speed of the second ball milling treatment is 450 rpm / min to 550 rpm / min, and the time of the second ball milling treatment is 55 h to 65 h, more preferably 60 h.

[0018] In a third aspect, the present invention provides a secondary battery, comprising the solid electrolyte according to the first aspect.

[0019] In a fourth aspect, the present invention provides an electrochemical device, comprising the secondary battery according to the third aspect.

[0020] The numerical range described in the present invention not only includes the point values ​​listed above, but also includes any point values ​​between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] The present invention provides a solid electrolyte, which can significantly improve the ionic conductivity of the solid electrolyte by doping non-metallic elements in a Li9N2Cl3-based solid electrolyte, using a non-metallic binary nitride composed of a trivalent, tetravalent or pentavalent non-metallic element and a nitrogen element to replace part of the Li3N in the solid electrolyte Li9N2Cl3 raw material, and further regulating its doping ratio. The doped and modified solid electrolyte provided by the present invention has a lower production cost than the original solid electrolyte, and has a higher ionic conductivity. DETAILED DESCRIPTION

[0023] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0024] Unless otherwise defined, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by technicians in the technical field to which the present invention belongs; the terms used in the specific implementation methods are only for the purpose of describing specific embodiments and are not intended to limit the present invention; the terms "including" and "having" in the description and claims of the present invention and any variations thereof are intended to cover non-exclusive inclusions.

[0025] In the description of the specific implementation methods of the present invention, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present invention, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.

[0026] Reference to "embodiments" in the present invention means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present invention. The appearance of the phrase in various places in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described in the present invention may be combined with other embodiments.

[0027] In the description of the embodiments of the present invention, the term "and / or" is only a description of the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in the present invention generally indicates that the associated objects before and after are in an "or" relationship.

[0028] Throughout the present invention, numerical values ​​represent approximate measures or limits of ranges to cover minor deviations from given values ​​as well as embodiments with about the values ​​mentioned and embodiments with the exact values ​​mentioned. Except for the working examples provided at the end of the detailed description, all numerical values ​​of parameters (e.g., amounts or conditions) in this specification (including the appended claims) should be understood to be modified by the term "about" in all cases, regardless of whether "about" actually appears before the numerical value. "About" indicates that the stated numerical value allows some minor imprecision (close to the exact value of the value to some extent; approximately or reasonably close to the value; almost). If the imprecision provided by "about" is not otherwise understood in this ordinary sense in the art, "about" as used in the present invention at least indicates the variation that can be produced by the ordinary methods of measuring and using such parameters. For example, "about" may include a variation of less than or equal to 5%, optionally less than or equal to 4%, optionally less than or equal to 3%, optionally less than or equal to 2%, optionally less than or equal to 1%, optionally less than or equal to 0.5%, and in some aspects, optionally less than or equal to 0.1%.

[0029] Additionally, disclosure of ranges includes disclosure of all values ​​within the entire range and further divided ranges, including endpoints and sub-ranges given for such ranges.

[0030] In one embodiment of the present invention, a solid electrolyte is provided, the chemical formula of the solid electrolyte is Li 9- 12x M1 ax N 2-4x+bx Cl3, where M1 is selected from non-metallic elements, a×a + =3b,a + is the valence of the M1 ion, a + is 3, 4 or 5, a>0, b>0 and the value range of x is 0.01~0.1.

[0031] In order to further obtain high-performance solid electrolytes, element doping is an important technical means, which plays an important role in the modification of solid electrolytes. It provides new ideas and methods for the development of high-performance solid-state batteries by improving ionic conductivity, improving electrochemical stability and enhancing structural stability. The effect of doping is also related to the radius and valence state of the doped ions. These factors will affect the structure and properties of solid electrolyte materials, thereby affecting their ionic conductivity. Therefore, when selecting the type of doping elements, it is necessary to consider the matching and optimization of these physical and chemical properties.

[0032] Li9N2Cl3-based solid electrolyte has a defective antifluoride structure (space group Fm 3ˉm), in which Li + Occupies tetrahedral sites [Li(N / Cl)4 tetrahedron], N 3+ and Cl - Randomly occupying the tetrahedral vertex sites, it is known that it has a disordered lattice structure and more vacancies, which provides more migration paths for lithium ions, thereby promoting the effective transmission of lithium ions. Based on this, the present invention uses trivalent, tetravalent or pentavalent non-metallic ions to replace part of the Li in the Li9N2Cl3-based solid electrolyte by doping non-metallic elements in the vacancy-enriched Li9N2Cl3-based solid electrolyte. + ions, and by further adjusting their doping ratio, the ionic conductivity of the solid electrolyte can be significantly improved. This is because the introduction of trivalent, tetravalent or pentavalent non-metallic ions can increase the number of ion channels, thereby improving the mobility of lithium ions.

[0033] In the present invention, the value range of x is 0.01 to 0.1, for example, it can be 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, etc. The above values ​​are only examples and are not limiting.

[0034] The present invention regulates the doping amount of non-metallic binary nitride in the solid electrolyte by controlling the value range of X, so that the doped solid electrolyte has higher ionic conductivity, and the cost of non-metallic binary nitride is lower than that of Li3N. By controlling the value range of X within this range, the non-metallic binary nitride replaces part of Li3N, which can further reduce the production cost.

[0035] In one embodiment, M1 is selected from one or more of silicon, boron, or phosphorus.

[0036] In one embodiment, M1 is selected from silicon, a + 4, the chemical formula of the solid electrolyte is Li 9- 12x Si 3x N2Cl3.

[0037] In one embodiment, M1 is selected from boron, a + 3, the chemical formula of the solid electrolyte is Li 9-12x B x N 2- 3x Cl3.

[0038] In one embodiment, M1 is selected from phosphorus, a + 5, the chemical formula of the solid electrolyte is Li 9-12x P 3x N 2+ x Cl3.

[0039] The present invention also provides a method for preparing the above-mentioned solid electrolyte, comprising the following steps:

[0040] The solid electrolyte is obtained by mixing and ball-milling a non-metallic binary nitride containing the M1 element, Li3N and LiCl.

[0041] In the present invention, the solid electrolyte is prepared by mixed ball milling, and no sintering treatment is performed. This is because the sintering treatment will increase the crystallinity of the material, which is not conducive to the synthesis of the solid electrolyte.

[0042] In the present invention, the ball milling process is performed under an inert atmosphere, which exemplarily includes at least one of argon or nitrogen.

[0043] In one embodiment, the non-metallic binary nitride containing the M1 element includes Si3N4, BN or P3N 5。

[0044] In one embodiment, the non-metallic binary nitride containing the M1 element is Si3N 4, Taking the total mass of Si3N4, Li3N and LiCl as 100%, the mass percentage of Si3N4 is 1%-10%, for example, 1%, 1.2%, 1.5%, 1.8%, 2%, 2.2%, 2.2%, 2.5%, 2.8%, 3%, 3.2%, 3.5%, 3.8%, 4%, 4.2%, 4.5%, 4.8%, 5%, 6%, 7%, 8%, 9%, 10%, etc. The above values ​​are for example only and are not limiting.

[0045] Si3N4 has a relatively low cost due to its wide application and relatively mature manufacturing process. Therefore, using Si3N4 to replace part of Li3N can control costs while improving the ionic conductivity of the doped solid electrolyte.

[0046] In one embodiment, the mixed ball milling includes: a first ball milling process and a second ball milling process.

[0047] In one embodiment, the rotation speed of the first ball milling treatment is 150 rpm / min to 200 rpm / min, for example, it can be 150 rpm / min, 160 rpm / min, 170 rpm / min, 180 rpm / min, 190 rpm / min, 200 rpm / min, etc.

[0048] In one embodiment, the first ball milling treatment lasts for 1 hour to 3 hours, for example, 1 hour, 1.5 hours, 2 hours, 2.5 hours, 3 hours, etc. The above values ​​are only examples and are not limiting.

[0049] In a preferred embodiment, the first ball milling treatment lasts for 2 hours.

[0050] In one embodiment, the ball milling cycle of the first ball milling treatment is: running for 3 to 5 minutes, such as 3 minutes, 4 minutes, 5 minutes, etc., and then stopping for 1 to 3 minutes, such as 1 minute, 2 minutes, 3 minutes, etc. The above values ​​are only examples and are not limiting.

[0051] Exemplarily, the first ball milling process satisfies any of the following conditions:

[0052] (a) First run at a speed of 150 rpm / min to 200 rpm / min for 3 minutes and then stop for 3 minutes.

[0053] (b) First run at a speed of 150 rpm / min to 200 rpm / min for 4 minutes and then stop for 2 minutes.

[0054] (c) First run at a speed of 150 rpm / min to 200 rpm / min for 5 minutes and then stop for 1 minute.

[0055] In the present invention, the particle size of the raw materials is reduced and the raw materials can be mixed uniformly by adjusting the rotation speed and time of the first ball milling process.

[0056] In one embodiment, the rotation speed of the second ball milling treatment is 450rpm / min to 550rpm / min, for example, it can be 450rpm / min, 460rpm / min, 470rpm / min, 480rpm / min, 490rpm / min, 500rpm / min, 510rpm / min, 520rpm / min, 530rpm / min, 540rpm / min, 550rpm / min, etc.

[0057] In one embodiment, the second ball milling treatment time is 55 hours to 65 hours, for example, 55 hours, 58 hours, 60 hours, 62 hours, 65 hours, etc. The above values ​​are only examples and are not limiting.

[0058] In a preferred embodiment, the second ball milling treatment lasts for 60 hours.

[0059] In one embodiment, the second ball milling process has a ball milling cycle of: running for 3 to 10 minutes, such as 3 minutes, 4 minutes, 5 minutes, 6 minutes, 7 minutes, 8 minutes, 9 minutes, 10 minutes, etc.; and then stopping for 10 to 17 minutes, such as 10 minutes, 11 minutes, 12 minutes, 13 minutes, 14 minutes, 15 minutes, 16 minutes, 17 minutes, etc. The above values ​​are only examples and are not limiting.

[0060] Exemplarily, the second ball milling process satisfies any of the following conditions:

[0061] (d) First run at a speed of 450 rpm / min to 550 rpm / min for 3 minutes and then stop for 17 minutes.

[0062] (e) First run at a speed of 450 rpm / min to 550 rpm / min for 4 minutes and then stop for 16 minutes.

[0063] (f) First run at a speed of 450 rpm / min to 550 rpm / min for 5 minutes and then stop for 15 minutes.

[0064] (g) First run at a speed of 450 rpm / min to 550 rpm / min for 7 minutes and then stop for 13 minutes.

[0065] (h) First run at a speed of 450 rpm / min to 550 rpm / min for 10 minutes and then stop for 10 minutes.

[0066] In the present invention, by adjusting the rotation speed and time of the second ball milling treatment, the raw material powder after the first ball milling is finely vibrated, mixed and ground again, so that it is easier to process and shape.

[0067] The present invention also provides a secondary battery, which comprises the solid electrolyte.

[0068] In one embodiment, the secondary battery further includes a positive electrode sheet and a negative electrode sheet.

[0069] In one embodiment, the positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer covering at least one side of the positive electrode current collector, and the positive electrode active material layer includes a positive electrode active material, a binder and a conductive agent.

[0070] It is understood that the present invention has no particular restrictions on the positive electrode current collector material, as long as it has conductivity and does not cause chemical changes in the battery. Exemplarily, the positive electrode current collector includes but is not limited to any one of aluminum, nickel or stainless steel, such as the positive electrode current collector is aluminum foil.

[0071] It is to be understood that the present invention has no particular limitation on the shape of the positive electrode current collector. Exemplarily, the shape of the positive electrode current collector includes but is not limited to metal foil, metal grid, metal mesh, and the like.

[0072] It is understood that the positive electrode active material is a compound that reversibly intercalates and deintercalates lithium, and the positive electrode active material in the present invention can be any positive electrode active material known in the art. Exemplarily, the positive electrode active material can be selected from lithium cobalt oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium manganese oxide, lithium iron manganese phosphate, lithium vanadium phosphate, lithium vanadium phosphate, lithium iron phosphate, lithium titanate or lithium-rich manganese elastic-based materials, etc.

[0073] In one embodiment, the negative electrode plate includes a negative electrode current collector and a negative electrode active material layer covering at least one side of the negative electrode current collector, and the negative electrode active material layer includes a negative electrode active material, a binder and a conductive agent.

[0074] It is understood that the present invention has no particular limitation on the negative electrode current collector material, as long as it has conductivity and does not cause chemical changes in the battery. Exemplarily, the negative electrode current collector includes but is not limited to any one of copper, nickel or stainless steel, such as the negative electrode current collector is copper foil.

[0075] It is to be understood that the present invention has no particular limitation on the shape of the negative electrode current collector. Exemplarily, the shape of the negative electrode current collector includes but is not limited to metal foil, metal grid, metal mesh, and the like.

[0076] It is understood that the negative electrode active material is a compound that reversibly intercalates and deintercalates lithium, and the negative electrode active material in the present invention can be any negative electrode active material known in the art. Exemplarily, the negative electrode active material can be selected from natural graphite, artificial graphite, hard carbon, soft carbon, silicon-based materials, titanium-based materials, tin-based materials, and metallic lithium, etc.

[0077] It is to be understood that the present invention does not specifically limit the type of conductive agent, and the positive electrode active material layer and the negative electrode active material layer may select the same conductive agent or different conductive agents. Exemplary, it includes at least one of carbon-based materials, powdered nickel or other metal particles or conductive polymers. For example, natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, channel black, acetylene black, carbon nanotubes, carbon nanofibers, polyaniline, polythiophene, polyacetylene, polypyrrole or poly (3,4-ethylenedioxythiophene) polystyrene sulfonate, etc.

[0078] It is understandable that the present invention does not specifically limit the type of binder. Without violating the concept of the present invention, the binder that can bond and maintain the active material, enhance the contact between the active material and the conductive agent and the active material and the current collector, and thus stabilize the pole piece structure is within the scope of protection of the present invention. The positive active material layer and the negative active material layer can choose the same binder or different binders. Exemplary, it contains thermoplastic resin or thermosetting resin. For example, polytetrafluoroethylene (PTFE), sodium carboxymethyl cellulose (CMC), styrene butadiene rubber (SBR), polyvinylidene fluoride (PVDF), nitrile rubber (NBR), styrene ethylene butylene styrene copolymer (SEBS), styrene butadiene styrene copolymer (SBS), lithium polyacrylate (LiPAA), sodium polyacrylate (NaPAA), sodium alginate, lithium alginate, etc.

[0079] In one embodiment, the above-mentioned solid electrolyte can be used as a solid electrolyte layer material, and the solid electrolyte layer can also include but is not limited to a polymer solid electrolyte, an oxide solid electrolyte or a sulfide solid electrolyte.

[0080] In specific applications, the sulfide solid electrolyte can be selected from: Li2S-P2S5, Li2S-P2S5-MS x (where M is Si, Ge and Sn and 0≤x≤2), Li 3.4 Si 0.4 P 0.6 S4, Li 10 GeP2S 11.7 O 0.3 , Li 9.6 P3S 12 、Li7P3S 11 、Li9P3S9O3、Li 10.35 Si 1.35 P 1.65 S 12 , Li 9.81 Sn 0.81 P 2.19 S 12 , Li 10 (Si 0.5 Ge 0.5 )P2S 12 、Li(Ge 0.5 Sn 0.5 )P2S 12 、Li(Si 0.5 Sn 0.5 )PsS 12 , Li 10 GeP2S 12(LGPS), Li6PS5X (where X is Cl, Br, or I), Li7P2S8I, Li 10.35 Ge 1.35 P 1.65 S 12 、Li 3.25 Ge 0.25 P 0.75 S4, Li 10 SnP2S 12 、Li 10 SiP2S 12 、Li 9.54 Si 1.74 P 1.44 S 11.7 C l0.3 、(1 - x)P2S 5-x Li2S (where 0.5 ≤ x ≤ 0.7), or at least one of them.

[0081] In a specific application, the halide solid electrolyte can be selected from: Li2CdC l4 、Li2MgC l4 、Li2Cd I4 、Li2ZnI4, Li3OCl, LiI, Li5ZnI4, Li3OCl 1-x Br x (where 0 < x < 1), or at least one of them.

[0082] In a specific application, the oxide solid electrolyte can be selected from: perovskite type, garnet type, LISICON type, NASICON type. Among them, the perovskite type solid electrolyte material is preferably LLTO (lithium lanthanum titanate, Li 0.33 La 0.56 TiO3), the garnet type solid electrolyte material is preferably LLZO (lithium lanthanum zirconate, Li7La3Zr2O 12 ), and the NASICON (sodium superionic conductor) type solid electrolyte material is preferably lithium aluminum titanium phosphate (LATPLi 1.3 Al 0.3 Ti 1.7 )(PO4)3), or at least one of them.

[0083] In one embodiment, the above solid electrolyte can be used as a reduction-resistant layer material, and the reduction-resistant layer can be disposed on the solid electrolyte layer, on the negative electrode layer, or separately between the solid electrolyte layer and the negative electrode layer.

[0084] In a preferred embodiment, the above-mentioned solid electrolyte material is used as a reduction-resistant layer material and is used in combination with a metallic lithium negative electrode. The above-mentioned solid electrolyte material has high reduction resistance and is characterized by being stable to Li and having high ionic conductivity. It can optimize the performance of the metallic lithium negative electrode, promote the application of lithium metal negative electrodes and the development of high-energy lithium metal batteries.

[0085] The beneficial effects of the present invention will be further illustrated below in combination with embodiments and comparative examples.

[0086] Example 1

[0087] This embodiment provides a chemical formula of Li 8.88 Si 0.03 A solid electrolyte of N2Cl3 and a preparation method thereof, wherein the preparation method comprises the following steps:

[0088] In a vacuum glove box filled with argon atmosphere, Li3N, LiCl and Si3N4 were added to a 80mL ZrO2 ball mill, wherein the total mass of Li3N, LiCl and Si3N4 was 3g, and the mass percentage of Si3N4 was 1% based on the total mass of Li3N, LiCl and Si3N4 being 100%. Then, 60g of ZrO2 ball milling beads (ZrO2 ball milling beads were selected from diameter ZrO2 ball milling beads and The ZrO2 ball milling jar was sealed and placed in a high-energy ball mill for the first ball milling at a speed of 150 rpm / min. The first ball milling time was 2 h, and the ball milling was stopped for 1 min after running for 5 min, and this cycle was repeated. Then, the second ball milling was carried out at a speed of 500 rpm / min. The second ball milling time was 60 h, and the ball milling was stopped for 15 min after running for 5 min, and this cycle was repeated to obtain Li 8.88 Si 0.03 N2Cl3 solid electrolyte powder particles.

[0089] Example 2

[0090] This embodiment provides a chemical formula of Li 8.64 Si 0.09 A solid electrolyte of N2Cl3 and a preparation method thereof, wherein the preparation method comprises the following steps:

[0091] In a vacuum glove box filled with argon atmosphere, Li3N, LiCl and Si3N4 were added to a 80mL ZrO2 ball mill, wherein the total mass of Li3N, LiCl and Si3N4 was 3g, and the mass percentage of Si3N4 was 3% based on the total mass of Li3N, LiCl and Si3N4 being 100%. Then, 60g of ZrO2 ball milling beads (ZrO2 ball milling beads were selected from diameter ZrO2 ball milling beads and The ZrO2 ball milling jar was sealed and placed in a high-energy ball mill for the first ball milling at a speed of 150 rpm / min for 2 h. After each first ball milling operation for 5 min, the ball milling was stopped for 1 min, and this cycle was repeated. Then, the second ball milling was carried out at a speed of 500 rpm / min for 60 h. After each second ball milling operation for 5 min, the ball milling was stopped for 15 min, and this cycle was repeated to obtain Li 8.64 Si 0.09 N2Cl3 solid electrolyte powder particles.

[0092] Example 3

[0093] This embodiment provides a chemical formula of Li 8.4 Si 0.15 A solid electrolyte of N2Cl3 and a preparation method thereof, wherein the preparation method comprises the following steps:

[0094] In a vacuum glove box filled with argon atmosphere, Li3N, LiCl and Si3N4 were added to a 80mL ZrO2 ball mill, wherein the total mass of Li3N, LiCl and Si3N4 was 3g, and the mass percentage of Si3N4 was 5% based on the total mass of Li3N, LiCl and Si3N4 being 100%. Then, 60g of ZrO2 ball milling beads (ZrO2 ball milling beads were selected from diameter ZrO2 ball milling beads and The ZrO2 ball milling jar was sealed and placed in a high-energy ball mill for the first ball milling at a speed of 150 rpm / min. The first ball milling time was 2 h, and the ball milling was stopped for 1 min after running for 5 min, and this cycle was repeated. Then, the second ball milling was carried out at a speed of 500 rpm / min. The second ball milling time was 60 h, and the ball milling was stopped for 15 min after running for 5 min, and this cycle was repeated to obtain Li 8.4 Si 0.15 N2Cl3 solid electrolyte powder particles.

[0095] Example 4

[0096] This embodiment provides a chemical formula of Li 7.8 Si 0.3 A solid electrolyte of N2Cl3 and a preparation method thereof, wherein the preparation method comprises the following steps:

[0097] In a vacuum glove box filled with argon atmosphere, Li3N, LiCl and Si3N4 were added to a 80mL ZrO2 ball mill, wherein the total mass of Li3N, LiCl and Si3N4 was 3g, and the mass percentage of Si3N4 was 10% based on the total mass of Li3N, LiCl and Si3N4 being 100%. Then, 60g of ZrO2 ball milling beads (ZrO2 ball milling beads were selected from diameter ZrO2 ball milling beads and The ZrO2 ball milling jar was sealed and placed in a high-energy ball mill for the first ball milling at a speed of 150 rpm / min. The first ball milling time was 2 h, and the ball milling was stopped for 1 min after running for 5 min, and this cycle was repeated. Then, the second ball milling was carried out at a speed of 500 rpm / min. The second ball milling time was 60 h, and the ball milling was stopped for 15 min after running for 5 min, and this cycle was repeated to obtain Li 7.8 Si 0.3 N2Cl3 solid electrolyte powder particles.

[0098] Example 5

[0099] This embodiment provides a chemical formula of Li 8.4 B 0.05 N 1.85 A solid electrolyte of Cl3 and a preparation method thereof, the preparation method comprising the following steps:

[0100] In a vacuum glove box filled with argon atmosphere, Li3N, LiCl and BN were added to a 80 mL ZrO2 ball mill, wherein the total mass of Li3N, LiCl and BN was 3 g, and the mass percentage of BN was 5% based on the total mass of Li3N, LiCl and BN being 100%. Then, 60 g ZrO2 ball milling beads (ZrO2 ball milling beads were selected from diameter ZrO2 ball milling beads and The ZrO2 ball milling jar was sealed and placed in a high-energy ball mill for the first ball milling at a speed of 150 rpm / min. The first ball milling time was 2 h, and the ball milling was stopped for 1 min after running for 5 min, and this cycle was repeated. Then, the second ball milling was carried out at a speed of 500 rpm / min. The second ball milling time was 60 h, and the ball milling was stopped for 15 min after running for 5 min, and this cycle was repeated to obtain Li8.4 B 0.05 N 1.85 Cl3 solid electrolyte powder particles.

[0101] Example 6

[0102] This embodiment provides a chemical formula of Li 8.4 P 0.15 N 2.05 A solid electrolyte of Cl3 and a preparation method thereof, the preparation method comprising the following steps:

[0103] In a vacuum glove box filled with argon atmosphere, Li3N, LiCl and P3N5 were added to a 80 mL ZrO2 ball mill, wherein the total mass of Li3N, LiCl and P3N5 was 3 g, and the mass percentage of P3N5 was 5% based on the total mass of Li3N, LiCl and BN being 100%. Then, 60 g of ZrO2 ball milling beads (ZrO2 ball milling beads were selected from diameter ZrO2 ball milling beads and The ZrO2 ball milling jar was sealed and placed in a high-energy ball mill for the first ball milling at a speed of 150 rpm / min. The first ball milling time was 2 h, and the ball milling was stopped for 1 min after running for 5 min, and this cycle was repeated. Then, the second ball milling was carried out at a speed of 500 rpm / min. The second ball milling time was 60 h, and the ball milling was stopped for 15 min after running for 5 min, and this cycle was repeated to obtain Li 8.4 P 0.15 N 2.05 Cl3 solid electrolyte powder particles.

[0104] Example 7

[0105] The difference between this embodiment and embodiment 1 is that, based on the total mass of Li3N, LiCl and Si3N4 being 100%, the mass percentage of Si3N4 is 20%, and the rest is the same as embodiment 1.

[0106] Comparative Example 1

[0107] This comparative example provides a solid electrolyte with a chemical formula of Li9N2Cl3 and a preparation method thereof, wherein the preparation method comprises the following steps:

[0108] In a vacuum glove box filled with argon atmosphere, Li3N and LiCl were added to a 80 mL ZrO2 ball mill, wherein the total mass of Li3N and LiCl was 3 g, and the mass percentage of Li3N was 1% based on the total mass of Li3N and LiCl being 100%. Then, 60 g ZrO2 ball milling beads (ZrO2 ball milling beads were selected from diameter ZrO2 ball milling beads and The ZrO2 ball milling jar is sealed and placed in a high-energy ball mill for the first ball milling at a speed of 150 rpm / min. The first ball milling time is 2 h, and the ball milling is stopped for 1 min after running for 5 min, and this cycle is repeated; then the second ball milling is carried out at a speed of 500 rpm / min. The second ball milling time is 60 h, and the ball milling is stopped for 15 min after running for 5 min, and this cycle is repeated to obtain Li9N2Cl3 solid electrolyte powder particles.

[0109] Test conditions

[0110] The solid electrolytes provided in Examples 1 to 7 and Comparative Example 1 were used to prepare a solid electrolyte membrane, and the solid electrolyte membrane was tested for physical and chemical properties. The test method is as follows:

[0111] Preparation of solid electrolyte membrane:

[0112] (1) Weighing polyvinylidene fluoride and the solid electrolyte powder particles provided in the above examples and comparative examples in a mass ratio of 1:10 and adding them into a small mixer at a rotation speed of 1000r and a temperature of 20°C for 45 minutes to obtain a uniformly mixed mixture;

[0113] (2) The mixed material is taken out and pre-kneaded to obtain a block, which is then placed in a roller press for hot rolling at a temperature of 90°C. The rollers are first rolled in a large roll gap state, and then the rolls are fed multiple times to gradually reduce the roll gap, and finally a solid electrolyte membrane with a target thickness of 50 μm is obtained.

[0114] Ionic conductivity test:

[0115] Take the solid electrolyte membrane prepared above and use a punching machine to punch out A disc of diameter (whose area is set to S) is placed in a solid electrolyte test mold, and a pressure of 200 MPa is applied. The pressure is kept constant for 1 min, and the prepared test mold sample is connected to the electrochemical workstation for impedance spectrum testing. The specific conditions are that the high-frequency zone parameters are set to 8 MHz, and the low-frequency zone parameters are set to 100 MHz. The test is started, and the test curve is fitted using Z-view software to obtain the impedance value R. After the test is completed, the solid electrolyte membrane is taken out, and the thickness is measured as L. The conductivity of the solid electrolyte membrane is calculated according to the following formula: σ = L / (R×S), and the unit is S / cm.

[0116] The test results are shown in Table 1:

[0117] Table 1

[0118] Solid electrolyte materials Nitride doping percentage (%) Ionic conductivity (S / cm) Example 1 <![CDATA[Li 8.88 Yes 0.03 N2Cl3]]> 1 <![CDATA[5.2×10 -5 ]]> Example 2 <![CDATA[Li 8.64 Yes 0.09 N2Cl3]]> 3 <![CDATA[6.7×10 -5 ]]> Example 3 <![CDATA[Li 8.4 Yes 0.15 N2Cl3]]> 5 <![CDATA[9.6×10 -5 ]]> Example 4 <![CDATA[Li 7.8 Yes 0.3 N2Cl3]]> 10 <![CDATA[1.8×10 -4 ]]> Example 5 <![CDATA[Li 8.4 B 0.05 N 1.85 Cl3]]> 5 <![CDATA[1.2×10 -4 ]]> Example 6 <![CDATA[Li 8.4 P 0.15 N 2.05 Cl3]]> 5 <![CDATA[2.6×10 -4 ]]> Example 7 <![CDATA[Li 6.6 Yes 0.6 N2Cl3]]> 20 <![CDATA[4.9×10 -5 ]]> Comparative Example 1 <![CDATA[Li9N2Cl3]]> 0 <![CDATA[4.2×10 -5 ]]>

[0119] It can be seen from Table 1 that according to Examples 1-6 and Comparative Example 1, the solid electrolyte material doped with non-metallic binary nitride has higher ionic conductivity, and has lower cost and higher ionic conductivity than the solid electrolyte Li9N2Cl3. According to Examples 1-4 and Example 7, by ensuring that the doping amount of non-metallic binary nitride is within 1%-10%, the doped solid electrolyte material can further obtain higher ionic conductivity.

[0120] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. A solid electrolyte, characterized in that The chemical formula of the solid electrolyte is Li 9-12x M1 ax N 2-4x+bx Cl3, where M1 is selected from non-metallic elements, a×a + =3b,a + is the valence of the M1 ion, a + is 3, 4 or 5, a>0, b>0 and the value range of x is 0.01~0.

1.

2. The solid electrolyte according to claim 1, characterized in that The M1 is selected from one or more of silicon, boron or phosphorus.

3. The solid electrolyte according to claim 2, characterized in that The M1 is selected from silicon, a + 4, the chemical formula of the solid electrolyte is Li 9-12x Si 3x N2Cl3.

4. A method for preparing a solid electrolyte according to any one of claims 1 to 3, characterized in that: The method comprises the following steps: The solid electrolyte is obtained by mixing and ball-milling a non-metallic binary nitride containing the M1 element, Li3N and LiCl.

5. The method according to claim 4, characterized in that The non-metallic binary nitride containing the M1 element includes Si3N4, BN or P3N 5。 6. The method according to claim 5, characterized in that The non-metallic binary nitride containing the M1 element is Si3N 4, Taking the total mass of Si3N4, Li3N and LiCl as 100%, the mass percentage of Si3N4 is 1%-10%.

7. The method according to claim 4, characterized in that The mixed ball milling includes: a first ball milling process and a second ball milling process.

8. The method according to claim 7, characterized in that The rotation speed of the first ball milling treatment is 150 rpm / min to 200 rpm / min, and the time of the first ball milling treatment is 1 h to 3 h, preferably 2 h; The rotation speed of the second ball milling treatment is 450 rpm / min to 550 rpm / min, and the time of the second ball milling treatment is 55 h to 65 h, preferably 60 h.

9. A secondary battery, characterized in that: The secondary battery comprises the solid electrolyte according to any one of claims 1 to 3.

10. An electrochemical device, characterized in that: The electrochemical device includes the secondary battery according to claim 9.